Characteristics measured by the Eating Disorder Inventory for children at risk and protective factors for disordered eating in adolescent girls - Sanna Aila Gustafsson; Birgitta Edlund; Lars Kjellin; et al (Dove Medical Press, 2010)
Sanna Aila Gustafsson1, Birgitta Edlund2, Lars Kjellin3, Claes Norring41Psychiatric Research Centre, School of Health and Medical Sciences, University of Örebro; 2Department of Public Health and Caring Sciences, University of Uppsala; 3Psychiatric Research Centre, University of Örebro; 4Centre for Psychiatry Research, Karolinska Institutet, Stockholm, SwedenObjective: The aim of this study was to examine longitudinally the role of characteristics measured by the Eating Disorder Inventory-Child version (EDI-C) to find early predictors that might constitute risk and protective factors in the development of disordered eating.Method: Participants were divided into three groups based on eating attitudes at T2: disordered eating (n = 49), intermediate eating concern (n = 260), and healthy eating attitudes (n = 120). EDI-C from T1 (four to five years earlier) was then analyzed to find predictors of group classification at T2.Results: Drive for thinness and body dissatisfaction emerged as risk factors at T1, while drive for thinness, body dissatisfaction, and interoceptive awareness emerged as protective factors after controlling for initial eating concerns and body mass index.Discussion: Eating disorders should not be seen as a result of a premorbid personality type. Rather we should take a more social-psychological perspective to explain how individual and sociocultural factors work together in the development of these conditions. Keywords: eating disorders, EDI-C, risk factors, protective factors